Private Costs of Patients Hospitalized with Community-Acquired Pneumonia. Issue 4 (3rd June 2005) - Jacobs, Philip; Marrie, Thomas J; Calder, Peter
Abstract : BACKGROUND: Community-acquired pneumonia (CAP) is a condition which frequently requires hospitalization and consequently, can result in high costs. Little is known of the additional personal resources that are used by patients hospitalized for CAP. OBJECTIVE: To measure the private costs for persons who were hospitalized with CAP for the 30 days after being admitted to hospital using a systematic method of measurement. METHODS: Potential personal cost items were identified by nurses familiar with the treatment of CAP and categorized. Using telephone interviews in conjunction with the cost-identification framework, 60 patients from the Edmonton, Alberta area were surveyed for their private costs associated with CAP for 30 days after admission to hospital. RESULTS: Of the 60 patients surveyed, 49 were older than 65 years of age. The mean private cost was $505, which amounted to 5.6% of the total societal costs of $8, 970. The distribution was skewed with a small number of patients that had high costs. CONCLUSIONS: This method allows the determination of the societal costs for patients hospitalized with pneumonia, and the costs were not much greater than those to the health care system.